Effect of caffeine citrate on diaphragmatic electrical activity in pre-term newborns - Tatiana B.B. Zidan; Eduardo J. Troster; Jennifer Beck; Livia R. Sanches; Carlos Eduardo S. Ferreira; Romy S.B. Zacharias; Celso M. Rebello (PLoS ONE, 2025)
The gold standard treatment for apnea of prematurity is caffeine citrate, which is known for its effect on diaphragm muscle activity. The purpose of this study was to investigate the electrical activity of the diaphragm in preterm newborns, which was measured 30 minutes before and 60 minutes after the administration of a loading dose of caffeine citrate. In this prospective, observational, longitudinal study at a tertiary-level neonatal ICU, data were collected from 36 patients (13 females, 23 males) with a mean gestational age of 31 2/7 ± 2 1/7 weeks and a mean birth weight of 1532 ± 439 grams. The average caffeine level was 15.7 ± 5.9 mg/dL (reference range: 5–30 mg/dL). The results revealed significant increases in all the parameters used to determine the inspiratory phases of the respiratory cycle postcaffeine administration (p < 0.001). The study concluded that caffeine administration significantly enhances diaphragmatic electrical activity in preterm newborns.